DNA Arrays with a Silver Lining. (17th August 2017) - Chandrasekaran, Arun Richard
Abstract: The development of molecular electronics is one of the current focuses of bottom‐up nanotechnology. DNA has been the building block for nanostructures with a variety of applications, and its use has been extended to the formation of conducting nanowires. The one‐dimensional silver/DNA hybrid arrays reported recently are a step towards achieving longer DNA nanowires. Abstract : Long, thin DNA "nanowires" can be created by silver‐mediated base pairs that form metallo‐base pairs C‐Ag‐C, G‐Ag‐G, G‐Ag‐C, and T‐Ag‐T. Interduplex connections provided by hybridization of overhangs lead to uninterrupted one‐dimensional silver–DNA hybrid arrays.